Design and implementation of a web-based replacement for the manual system of moderating exams - Oladokun, Adeola Asiat (2014)
Moderation of exam paper/coursework is an important process that provides a framework for ensuring that examinable materials are designed in accordance with the learning outcome of the program description. Performing this process using paper-based method creates delay in transferring the printed moderation documents among users and incurs cost in terms of printing and posting of documents. This work designed and developed a more efficient web-based system to replace the paper-based process of performing moderation. Web engineering, an approach that supports the development of scalable and maintainable web-based systems was used in developing the system. The system was implemented using CakePHP framework which follows the Model View Controller (MVC) design paradigm together with MySQL database for storing the moderation documents hosted on WAMP server. After developing the system, evaluation was conducted by users to verify that the system meets the users need. The result obtained from the evaluation showed that 54% of the users agreed that the system provided the functionalities necessary for performing the moderation of exam paper/coursework. Also, where time permitted, the improvements suggested by users were implemented which tailored the functionalities of the system towards user satisfaction.